Notes on factor price equality and biased technical change in a two-cone trade model - Daniel Thomas Becker; Erich Gundlach (Kiel Institute for the World Economy (IfW), 2006)
We reconsider the effects of long-run economic growth on relative factor prices across cones of specialization. We model economic growth as exogenous technical change. Allowing for capital biased technical change with a sector bias and for endogenous commodity prices, we find that economic growth may increase or decrease factor price differences across cones. For a neutral demand side and capital biased growth in the most capital intensive sector, we find that economic growth encourages less factor price diversity across cones.
Keywords: F11; O40; 330; Economic growth; Two cone trade model; Factor price equality; Faktorpreisausgleich; Wirtschaftswachstum; Technischer Fortschritt; Bias; Außenwirtschaftstheorie; Theorie